Modes of corporate liability for money laundering and financing of terrorism (2016)
In this study, corporate liability in respect of money laundering and the financing of terrorism will be examined. The paper discusses the concept of corporate liability. The third part discusses terrorism which is further divided into five segments. The first segment traces the history of terrorism. The second segment discusses issues in defining terrorism. The third segment discusses the definition of terrorism in Nigeria while the fourth segment catalogues some terrorist activities in Nigeria. The fifth segment discusses cyber terrorism as a distinct form of terrorism. The fourth part of the study discusses money laundering together with the financing of terrorism. The paper advocates a shift of focus from theoretical debate to practical issue of utility and concludes that corporate governance must make meaningful impacts on the life of all the stakeholders.